Association between metallic implants and stroke in US adults from NHANES 2015–2023 a cross-sectional study - Kai Wu; Liang Pang; Pingping Su; Cunxian Lv (Frontiers in Aging Neuroscience)
ObjectiveMetal implants play a vital role in orthopedic treatment and are widely used in fracture repair, joint replacement and spinal surgery. Although these implants often contain key elements such as chromium (Cr), their potential health effects, particularly their association with stroke risk, have not been fully elucidated. This study aimed to evaluate the association between metallic implants and stroke.MethodsUsing data from the 2015 to 2023 National Health and Nutrition Examination Survey (NHANES), we conducted a cross-sectional analysis of 12,337 US adults, in which 3,699 participants reported having metal implants and 8,638 without. Implant-like.ResultsThrough logistic regression analysis, we revealed a significant positive association between metallic implants and stroke risk (adjusted OR = 1.458, 95%CI (1.130, 1.881), p = 0.004). Further stratified analysis found that this positive association was more significant among older and less physically active participants.ConclusionFindings suggest that metallic implants may be associated with an increased risk of stroke, but given the inherent limitations of cross-sectional studies, this study cannot establish causality.